MONITORING LEVEL KETINGGIAN AIR SEBAGAI PERINGATAN DINI BENCANA BANJIR BERBASIS SMS - Budi Amri; Sukrina (J-Innovation, 2016)
Monitoring of water level as aflood disaster early warning based on SMS uses arduino as a controller of all systems. electronic devices that have important roles in this system consistof probe sensors as the altitude and low tidedetector, GSM SIM 900A module as a sending mediator to handphone, and arduino as a system controller. The Warning information consists of standby-1 for the water level of 0cm-20cm, standby-2 for the water level of 20cm-30cm, and standby-3 for water level 30cm-50 cm. The three water levels are detected by the probe sensor. When the water touches the sensor, the sensor sends the data to be processed by arduino, then arduino commands GSM SIM 900A Module to send SMS to handphone in the form of water level warning and status. Besides sending the SMS as a warning status, arduino also send a warning signal in the form of buzzer sound when water level is in standby-2 and standby-3.